Methodology of the French National Study “Context of Sexualities in France” ( CSF ‐2023) - Caroline Moreau; Aline Bohet; Armelle Andro; Yann Le Strat; Nathalie Bajos (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Introduction The 2023 national survey “Context of Sexualities in France” (CSF‐2023) explores sexuality and sexual health in France. Methods Conducted between November 2022 and December 2023, CSF‐2023 is a cross‐sectional probability survey involving 21,259 respondents aged 15–89 in continental France. Participants were selected via random‐digit dialing, completing a 33‐min phone interview (Part 1), followed by a 30‐min self‐administered online questionnaire for those 18 and older (Part 2). Sexually active respondents aged 18–59 also participated in a sexually transmitted infection (STI) self‐testing study. The survey collected data on sociodemographic characteristics, sexual attitudes, relationships, practices, gender expressions, and digital use for self‐care and sexual practices. Results A total of 21,259 individuals completed the Part 1 survey (34% response rate). Of those, 12,906 individuals aged 18–89 completed Part 2 (71% of the 18–89 eligible group). Among the 13,686 individuals aged 18–59 offered STI testing, 4872 (32%) returned results; of the 2959 aged 18–29 offered Human Papillomavirus (HPV) testing, 811 (27%) participated. Post‐stratification weights were applied to mitigate non‐response bias for key sociodemographic traits, with minimal impact on sexual and reproductive health (SRH) indicators, reaffirming sample representativeness. Fieldwork highlighted the importance of not only adapting questionnaire design and sequencing, but also providing strong psychological and supervisory support to interviewers administering a large‐scale survey on sensitive and sometimes distressing topics. Conclusion CSF‐2023 provides rich data to track trends in sexuality and sexual health in France, while expanding knowledge on emerging topics such as digital sexual health and SRH self‐care. These findings can inform policy and programming, including the French National Strategy for Sexual Health and the World Health Organization European action plan for SRH. In parallel, the CSF‐2023 fieldwork experience provides important methodological insights into the conduct of large‐scale sexual health research, underscoring the central role of interviewer training, supervision, and psychological support in ensuring high‐quality data collection on sensitive topics.